EKSTRAK KULIT BAWANG MERAH (Allium ascalonicum) SEBAGAI ANTIBAKTERI UNTUK PENGOBATAN UDANG VANAME YANG DIINFEKSI Vibrio parahaemolyticus - Ramadhani, Dian Eka; Wahjuningrum, Dinamella; Saputri, Rika Ani; Widanarni, Widanarni; Rizkiyanti, Ita (Politeknik Kelautan dan Perikanan Jembrana, 2024)
Early Mortality Syndrome (EMS) or Acute Hepato Pancreatic Necrosis Disease (AHPND) caused by the pathogenic bacteria Vibrio parahaemolyticus (V. par) causes mass deaths in shrimp farming. This study aims to obtain the effective dose of shallot skin extract as a treatment for Pacific whiteleg shrimp infected with V. par RfR (rifampicin resistance 50 µg mL- 1). This research was conducted at the Pilot plane Faculty of Agricultural Technology and Laboratory of Aquatic Animal Health Management, Jepara Centre for Brackish Water Aquaculture (BBPBAP). This study used a Completely Randomized Design (CRD) consisting of five treatments and three replications, namely K- (negative control), K+ (positive control), KBM6,25 (shallot skin extract 6,25%), KBM12,5 (shallot skin extract red 12,5%), and KBM25 (shallot skin extract 25%). This research used Pacific whiteleg shrimp 3,41 ± 0,73 g fish-1,which were injected with V. par RfR bacteria and continued with 14 days of maintenance. The results showed that administration of shallot skin extract at a dose of 6,25% resulted in total haemocyte count (THC), differential haemocyte count (DHC), phagocytic activity (AF), reduction in the number of V. par RfR bacteria, survival rate, and feeding ratio which were significantly different compared to the positive control. Meanwhile, the clinical symptoms caused by treatment with shallot skin extract at doses of 6,25%, 12,5% and 25% recovered on the 14th day compared to the positive control, which still experienced clinical symptoms of infection.